Contribuições interventivas e os limites jurídicos da atuação do estado no domínio econômico - Beltrão, Demetrius Amaral (2011)
This study aims at analyzing in a critical manner the extra taxation and the State intervention, through taxation, in the economy. The subject-matter are interventional contributions in the economic domain and, more specifically, the reading of the normative model provided by the Federal Constitution, seeking an analysis of the validity criteria of actions from the Public Authority which are immediately related to an indirect role of the State in the economic scope. The theme introduction in these terms does not imply disregarding a more natural point of view when dealing with constitutionality questions of validity and control of instituting rules of such exactions, but move on especially to identify and define the limits legally imposed to the State with regard to the institution of those contributions. The systematic set of constitutional rules and principles which are to be verified in order to identify the criteria mentioned herein will not be restricted to what can be defined from the Federal Constitution chapters which are referred to the taxation, but also and mainly, from the chapter related to the economic order, specially the principles of free enterprise and free competition. Considering the subject-matter of the study herein, it is mandatory to have a preliminary approach of the historical evolution of the economic in the Constitutions, of the economic law concept which will be viewed as a self-contained deployment of the Public Law and it is featured by the existence of specific law principles, non-subject to the application in other areas , as well as the conception of State adopted by the Constitution of 1988, with respect to the possibilities of its role in the economic field. In this context, it shall be necessary to examine the general models theoretically designed about the extension and the limits of the State intervention in the economy and, mainly in the case of Brazil, which intervention forms are accepted by the Constitution relatively to the State in the economy. The contribution (tax) based on the State intervention is found right among these formulas, whose profile shall be identified as well as the parameters and criteria which shall be used in order to identify the limits legally imposed to the State power with regard to the institution of these interventional contributions.